2000
DOI: 10.1109/16.830981
|View full text |Cite
|
Sign up to set email alerts
|

High voltage GaN Schottky rectifiers

Abstract: Mesa and planar GaN Schottky diode rectifiers with reverse breakdown voltages (V~~) up to 550V and >2000V, respectively, have been fabricated. The on-state resistance, RON, was 6mQ.cm2 and 0.8Llcmz, respectively, producing figure-of-merit values for (VRB)2/RoN in the range 5-48 MW.cm-2. At low biases the reverse leakage current was proportional to the size of the rectifying contact perimeter, while at high biases the current was proportional to the area of thk contact. These results suggest that at low reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 18 publications
0
40
0
1
Order By: Relevance
“…Due to its unipolar nature, a Schottky diode does not exhibit the minority carrier storage effect, thus faster switching speed and less reverse recovery current can be achieved with Schottky diodes compared to p-n junction diodes. Due to the poor availability of bulk GaN substrates, GaN-based Schottky rectifiers have been fabricated using GaN films epitaxially grown on foreign substrates such as sapphire [11][12][13][14][15][16][17]. Zhang et al has reported a record V B value of 6350 V for Schottky rectifiers fabricated laterally on GaN epitaxial layer grown on sapphire [17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its unipolar nature, a Schottky diode does not exhibit the minority carrier storage effect, thus faster switching speed and less reverse recovery current can be achieved with Schottky diodes compared to p-n junction diodes. Due to the poor availability of bulk GaN substrates, GaN-based Schottky rectifiers have been fabricated using GaN films epitaxially grown on foreign substrates such as sapphire [11][12][13][14][15][16][17]. Zhang et al has reported a record V B value of 6350 V for Schottky rectifiers fabricated laterally on GaN epitaxial layer grown on sapphire [17].…”
Section: Introductionmentioning
confidence: 99%
“…Impressive high voltage operation of AlGaN/GaN field effect transistors (FETs) and GaN-based rectifiers continue to be reported [1]- [3]. However, no GaN-based heterojunction bipolar transistors (HBTs) with operation voltage higher than 100 V have been presented.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them include [87][88][89][90][91] † The lack of native oxide in GaN restricts production of GaN MOS devices. However, SiC uses SiO 2 as a native oxide.…”
Section: Silicon Carbide Against Gallium Nitridementioning
confidence: 99%